Children and Families’ Experiences with Document Portability, Security and Verification During Forced Migration - Ungar, Michael; Kuru, Nilüfer; Tashkinova, Oksana (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2026)
This qualitative study explores the experiences of forcibly displaced families and their strategies for protecting and transporting identity, health, and education records during migration. Ninety in-depth, semi-structured interviews were conducted with parent–child dyads who had been displaced from Afghanistan, Syria, and Ukraine and currently residing in Türkiye, Poland, and Canada. Findings revealed that documents not only served legal and practical purposes but also symbolized memory, safety, and familial continuity. Mothers emerged as the primary guardians of official records. The study highlights the urgent need for accessible, secure, and inter-operable document storage systems that reflect the lived realities of displaced families.